Islamic Coping, Post Traumatic Stress Disorder (PTSD) and Islam Oriented Trauma Focused Cognitive Behavioral Therapy (IO-TF-CBT) in Post-Kahramanmaraş Earthquake Period - Metin Çınaroğlu (Eskiyeni, 2024)
The Great Southeast Turkey Earthquakes (GSTE) of February 2023 were not only a physical disaster but also seem to have triggered the onset of Post-Traumatic Stress Disorder (PTSD) among survivors in Kahramanmaraş and surrounding areas. This review emphasizes the need for culturally appropriate clinical interventions in PTSD therapies, addressing the psychological impacts left by the earthquakes. The Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) models implemented after the 1999 Marmara earthquake failed to integrate cultural and Islamic thoughts effectively. With this critical perspective, the article advocates for a holistic healing process that integrates Islamic coping mechanisms with clinical psychology. The importance of religious and spiritual practices in PTSD recovery, especially reliance on Allah, patience, the concept of ummah, prayer, almsgiving, and belief in destiny, is highlighted. While analyzing the potential effectiveness of Islamic approaches in PTSD rehabilitation, the study criticizes the inadequacies of current clinical practices and advocates for the adoption of faith-integrated therapeutic strategies. It proposes a structured methodology for Islamic-Oriented TF-CBT that integrates spiritual practices with scientifically supported psychological interventions, highlighting the gaps in current practices. The aim is to bridge the gap between Islamic practices and clinical psychology, offering a treatment approach compatible with the religious values and traditions of the Muslim population affected by the GSTE. This critical perspective strengthens the call for progress towards cultural competency in mental health services, ensuring that PTSD treatments adapt to the diversity and complexity of earthquake victims. The article emphasizes the need to comprehensively address the psychological needs of individuals affected by the GSTE, particularly those battling PTSD. Recognizing PTSD as not only an individual disorder but also a societal issue, the study suggests that treatment processes should consider not only the individual but also the community. The importance of community-based interventions is highlighted, discussing the current shortcomings and areas for development in this field. In conclusion, the article underscores the significance of cultural sensitivity and community-based approaches in PTSD treatment, calling for more research and implementation in this area.